Regulation of SPDEF expression by DNA methylation in advanced prostate cancer - Vatanmakanian, Mousa; Steffan, Joshua J.; Koul, Sweaty; Ochoa, Augusto C.; Chaturvedi, Lakshmi S.; Koul, Hari K. (Frontiers in Endocrinology, 2023)
Expression of SPDEF, an Ets transcription factor, suppresses prostate cancer cell migration, invasion, and metastasis in experimental tumor models. We observed that the expression of SPDEF decreases during the progression and metastasis of prostate cancer. The mechanism by which SPDEF is silenced in advanced-stage prostate cancer is unclear. In this report, we observed that: a) there is a gradual decrease in SPDEF expression with a concomitant increase in methylated CpG sites within the SPDEF gene during prostate cancer progression from lower to higher Gleason grade; b) Expression of DNMT’s (DNMT1, 3a and 3b) is increased during prostate cancer progression, and there is an inverse correlation between SPDEF and DNMT expression; c) SPDEF levels are decreased in RC77/T, a line of PCa cells from African American origin similar to PC3 and DU145 cells (CRPC cells), as compared to LNCaP cells , a line of androgen dependent cells,; d) the 5′ CpG island of SPDEF gene are hypermethylated in SPDEF-negative CRPC ( PC3, DU145 and RC77/T) cell lines but the same regions are hypomethylated in SPDEF-positive castrate sensitive (LNCaP) cell line ; (e) expression of SPDEF in PCa cells lacking SPDEF decreases cell migration and invasion, but has no significant effect on cell proliferation, and; (f) treatment with the demethylating agent, 5-aza-2′-deoxycytidine, or silencing of the DNMT’s by siRNA, partially restores SPDEF expression in SPDEF-negative PCa cell lines, and decreases cell migration and invasion. These results indicate hypermethylation is a prevalent mechanism for decreasing SPDEF expression during prostate cancer progression. The data demonstrate that loss of SPDEF expression in prostate cancer cells, a critical step in cellular plasticity, results from a potentially reversible process of aberrant DNA methylation. These studies suggest DMNT activity as a potential therapeutic vulnerability that can be exploited for limiting cellular plasticity, tumor progression, and therapy resistance in prostate cancer.